Why young people attempt suicide in India: A qualitative study of vulnerability to action - Madhumitha Balaji; Kavita Mandhare; Kalyani Nikhare; Arjun K. Shah; Prajakta Kanhere; Smita Panse; Manjeet Santre; Lakshmi Vijayakumar; Michael R. Phillips; Soumitra Pathare; Vikram Patel; Katarzyna Czabanowska; et al. (Elsevier, 2023)
Suicidal behaviours among young people in India are a major public health problem. An understanding of the reasons for suicide attempts from survivor perspectives is essential to developing suicide prevention programs for this population, as these can provide valuable insights into concerns that are unique to young people, and direct the focus of such programs towards these specific concerns. Qualitative studies are best suited for eliciting such perspectives, but such studies in India are lacking. We conducted semi-structured interviews with 47 persons between the ages of 15 and 29 who had been admitted to a public hospital in Pune, India, following a suicide attempt. Participants were asked to describe in their own words, what they believed was the reason for the attempt. Data was analysed using inductive thematic analysis and summative content analysis. There were three broad factors that interacted to lead to suicide attempts - background factors (individual and environmental factors that increased vulnerability); psychological distress (emotional and cognitive states that led to suicidal ideation); and intervening factors (factors that facilitated transition from distress to the attempt). The most common pattern was the occurrence of an interpersonal stressor shortly before the attempt, which produced distorted cognitions, and overwhelming emotions - usually of anxiety or anger - with ready access to means and/or impulsivity being the final catalysts. This stressor was generally a trigger associated with long-standing problems involving partners or family members, which had already produced intolerable distress over time. Female participants appeared particularly vulnerable to these stressors, partly due to prevailing socio-cultural norms. Our findings suggest the need for suicide prevention programs in India to foster life skills for young people, engage with high-risk groups (for example, women), and restrict access to harmful substances. Family stakeholders need to be involved in the implementation.